Effects of continuous or intermittent ractopamine HCl (paylean1) use on pig growth performance in late finishing - Neill, C.R.; Groesbeck, C.N.; Brown, K.R.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 110 barrows (PIC L210 × L42) with an initial weight of 154.4 lb were used in a 56-d feeding trial to evaluate the effects of continuously feeding ractopamine HCl (Paylean; 9 g/ton), withdrawing Paylean, or intermittent Paylean feeding on finishing pig performance. There were five experimental treatments fed the last 56 d before marketing; A) control diet (no Paylean) fed for 56 d; B) Paylean diet (9 g/ton) fed for 56 d; C) Paylean fed for 21 d, control for 14 d, then Paylean for 21 d; D) control fed for 7 d, Paylean fed for 21 d, control fed for 7 d, then Paylean fed for 21 d; and E) control fed for 35 d, then Paylean fed for 21 d. Pigs fed Paylean for 21 d then withdrawn for 7 or 14 d and then re-fed for 21 d (Treatments C and D) had similar response to those fed Paylean for only the last 21 d before market (Treatment E). Pigs fed these three treatments had final weight numerically increased by 3 to 5 lb over that of pigs continuously fed Paylean for the entire 56 d. During the period when Paylean was withdrawn (7 or 14 d), pigs lost much of the benefit that had been gained from Paylean feeding. But pigs fed Paylean again later seem to respond similarly to pigs that had never had Paylean in the diet.
Swine research, 2005 is known as Swine day, 2005
Keywords: Finishing pig; Paylean; Withdrawal; Swine